Induction of telomerase activity by irradiation in human lymphoblasts - Neuhof, Dirk; Rueß, Alexandra; Wenz, Frederik; Weber, Klaus-Josef (Radiation research, 2001)
Neuhof, D., Ruess, A., Wenz, F. and Weber, K. J. Induction of Telomerase Activity by Irradiation in Human Lymphoblasts. Radiat. Res. 155, 693-697 (2001). Telomerase activity is a radiation-inducible function, which suggests a role of this enzyme in DNA damage processing. Since the tumor suppressor TP53 plays a central role in the regulation of the cellular response to DNA damage, our study explored the ability of ionizing radiation to change telomerase activity and telomere length in two closely related human lymphoblast cell lines with different TP53 status. TK6 cells (wild-type TP53) and WTK1 cells (mutated TP53) were exposed to different doses of X rays, and telomerase activity was measured by PCR ELISA at different times after irradiation. A dose-dependent increase in telomerase activity was observed. One hour after irradiation with 4 Gy, TK6 and WTK1 cells showed an approximately 2.5-fold increase; for lower doses (0.1 to 1 Gy), telomerase induction was seen only in TK6 cells. Telomerase induction was observed by 0.5 h after irradiation, with a further increase up to 24 h. Irradiated TK6 and WTK1 cells had longer telomeres (+1.3 kb) than unirradiated cells 14 days after exposure. Our data demonstrate a dose-dependent induction of telomerase activity and lengthening of telomeres by ionizing radiation in human lymphoblasts. Induction of telomerase activity by radiation does not generally appear to be controlled by the TP53-dependent DNA damage response pathway. However, for low doses, induction of telomerase requires wild-type TP53.